2010
DOI: 10.1098/rstb.2009.0250
|View full text |Cite
|
Sign up to set email alerts
|

Organization and expression of organellar genomes

Abstract: Protist mitochondrial genomes show a very wide range of gene content, ranging from three genes for respiratory chain components in Apicomplexa and dinoflagellates to nearly 100 genes in Reclinomonas americana . In many organisms the rRNA genes are fragmented, although still functional. Some protist mitochondria encode a full set of tRNAs, while others rely on imported molecules. There is similarly a wide variation in mitochondrial genome organization, even among closely related groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 101 publications
2
60
0
Order By: Relevance
“…We therefore anticipated modest changes in the levels of organelle-encoded transcripts. Mitochondrial genomes encode proteins that function in mitochondrial processes, particularly translation and oxidative phosphorylation (41). Examination of transcripts from ise1 and ise2 mutants revealed that numerous mitochondria-encoded genes are induced (Table 3); strikingly, different genes are affected in each mutant.…”
Section: Ise2 Is Found In Chloroplastsmentioning
confidence: 99%
“…We therefore anticipated modest changes in the levels of organelle-encoded transcripts. Mitochondrial genomes encode proteins that function in mitochondrial processes, particularly translation and oxidative phosphorylation (41). Examination of transcripts from ise1 and ise2 mutants revealed that numerous mitochondria-encoded genes are induced (Table 3); strikingly, different genes are affected in each mutant.…”
Section: Ise2 Is Found In Chloroplastsmentioning
confidence: 99%
“…The shift from a single to a multipartite chromosomal architecture has happened many times in mtDNA evolution but is a surprisingly rare event for ptDNAs (12). No fewer than 12 eukaryotic lineages are known to contain fragmented mitochondrial genomes, and mtDNA splintering has transpired more than once within certain groups, including cnidarians (48), chlamydomonadalean algae (44), and vascular plants (13,49).…”
Section: A Multiplicity Of Mitochondrial and Plastid Genome Architectmentioning
confidence: 99%
“…Chlamydomonadalean mtDNAs also have diminished coding contents (10-13 genes) (44), and some land plants (e.g., S. moellendorffii), animals (e.g., the winged box jellyfish), and trypanosomes have lost all or most of their mitochondrial tRNA-coding regions (39,42,48). Plastid genomes are typically more gene-rich than mtDNAs (12), maxing out at ∼250 genes in red algae (69). Plants and algae that have lost photosynthetic capabilities have reduced plastid gene contents (<75) (63,64,70), but the absolute lowest are in the photosynthetic, peridinin plastids of dinoflagellates, which encode <20 genes (62).…”
Section: A Multiplicity Of Mitochondrial and Plastid Genome Architectmentioning
confidence: 99%
See 2 more Smart Citations